(untitled) (Czech Journal of International Relations, 2002)
The Contemporary Czech discussion on the European Security and Defense Policy (ESDP) is dealing with issues, which are either overly focused on the Czech Republic (CR), or else no longer considered topical by the rest of Europe. Neither the problems in participation for countries like the CR, nor hesitancy about the need to construct an ESDP, are very interesting for Europe. The current European debate on the ESDP is focused on a different set of problems. And if the CR wants to maintain any influence on the development of this EU policy, it should get involved in it. Some circles in the current EU discussion are more concerned about the longer-term direction and support the basic principles of the ESDP, limiting the political ambitions of the EU’s security and military activities, which could reappear in the formulation of specific doctrines for EU operations and individual priorities for their use in various parts of the world. The second type of problems being discussed is directed more towards the medium-term consequences of a rapid development of institutions and instruments for this new EU policy, including the expectation of quick results. Among these would be the functioning of the EU, especially in terms of consequences for the current EU Common Foreign and Defense Policy. These concerns about the possible consequences of present EU decisions also touch upon the issue of possessing sufficient means and resources to ensure the security and defense of the EU. The third set of questions deals with the practical problems hampering the development of the EU in the security field. These are primarily concerned with the blocking of agreements defining the cooperation between the EU and NATO, which are being held hostage by Turkey (at times by Greece and France as well). Unless an acceptable compromise can be reached, the Turkish objection will block or limit EU activity well into the future. Some consideration on the part of the Czechs about their own priorities and preferences in this long-term discussion should begin very soon, for this would help clarify Czech policy and contribute to the inclusion of the Czech Republic in the pan-European security debate.